Characterization Of Multilayer ZnO/METAL/ZnO As pH Sensor - Rasheed, Hiba Saad (2019)
This study focused on the synthesis and characterisation of ZnO/metal/ZnO multilayer thin films for extended gate field effect transistors in pH sensor devices by using a physical method. Multilayer structures ZnO/metal/ZnO and ZnO single layer were deposited on glass substrate via radio frequency and direct current magnetron sputtering.